1979
DOI: 10.3758/bf03196940
|View full text |Cite
|
Sign up to set email alerts
|

Simple drawing and pattern completion techniques for studying visualization and long-term visual knowledge

Abstract: Simple and efficient drawing and completion tasks for studying visual memory are developed. In Experiment 1 subjects reproduced a series of matrix patterns by filling empty matrices. The serial position function was flat, except that accuracy was much higher for final patterns. In Experiment 2 this recency effect was removed by an interpolated pattern classification task. Experiments 3 and 4 examined the effect of counting backward during intervals of from 3 to 15 sec on the recall of single patterns. Drawings… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
27
0
1

Year Published

1985
1985
2016
2016

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(30 citation statements)
references
References 20 publications
2
27
0
1
Order By: Relevance
“…Indeed, Christie and Phillips (1979) deliberately set out to show that their conceptualisation of visual remembering extends to drawing as a test of memory.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, Christie and Phillips (1979) deliberately set out to show that their conceptualisation of visual remembering extends to drawing as a test of memory.…”
Section: Discussionmentioning
confidence: 99%
“…The processing task impaired memory compared to a condition with unfilled RI, but did not lead to faster forgetting over time. Christie and Phillips (1979) asked participants to reproduce patterns of randomly filled grids after variable RIs during which they counted backwards in steps of three. Distractor processing reduced memory compared to a condition with unfilled RI, but the duration of the RI had no effect, mirroring the findings of Oberauer andLewandowsky (2013, 2014) with verbal memoranda combined with non-verbal distractor, which also found that memory was unaffected by the duration for which the distractor task had to be carried out.…”
Section: Retention Interval and The Amount Of Distractor Processing (mentioning
confidence: 99%
“…While a lot of research has examined the functions and characteristics of the phonological loop (e.g., Vallar & Baddeley, 1982;Burani, Vallar, & Bottini, 1991), the visuospatial sketchpad has received less attention and its mechanisms ate notas well understood (see also Logie, 1986). In fact, despite the growing evidence for the working memory model several aspects concerning the visuospatial sketchpad require further specification: For example, based on interference effects obtained in dual task paradigms, several researchers have doubted the existence of a posticon temporary store of visual information and have suggested that general resources ate involved in encoding and processing of visuospatial information (Christie & Philips, 1979). In addition, it remains to be specified whether the visuospatial sketchpad is a unitary systern or is composed of different subcomponents, specialized for the processing of different aspects of visual information.…”
Section: Introductionmentioning
confidence: 97%